2023
DOI: 10.1021/acsami.3c02761
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Impact-Resistant Composites with Bioinspired Three-Dimensional Solid–Liquid Lattice Designs

Abstract: The ubiquitous solid−liquid systems in nature usually present an interesting mechanical property, the rate-dependent stiffness, which could be exploited for impact protection in flexible systems. Herein, a typical natural system, the durian peel, has been systematically characterized and studied, showing a solid−liquid dual-phase cellular structure. A bioinspired design of flexible impact-resistant composites is then proposed by combining 3D lattices and shear thickening fluids. The resulting dual-phase compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Mechanical and recovery properties of CIS structure. (a) Ashby map of CIS structures mechanical properties design pattern (Figure S20, Supporting Information). (b) Application for lander legs.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical and recovery properties of CIS structure. (a) Ashby map of CIS structures mechanical properties design pattern (Figure S20, Supporting Information). (b) Application for lander legs.…”
Section: Resultsmentioning
confidence: 99%
“…The use of composite materials to improve the mechanical properties of MJ-printed lattice structures is widespread. It was observed that the compressive stress [33], tensile stress [34], impact resistance and energy absorption properties [35,36] of lattice structures fabricated with different composite materials via MJ were significantly strengthened. On the other hand, in addition to the use of composite materials, hybrid designs have also been used in recent years to improve the mechanical properties of these lattice structures [37].…”
Section: Introductionmentioning
confidence: 99%